2013
DOI: 10.4236/jct.2013.41018
|View full text |Cite
|
Sign up to set email alerts
|

Quality of Life (QOL) in Long-Term Survivors of Osteosarcoma

Abstract: We conducted this study to analyze the quality of life using the SF-36 health questionnaire and the MSTS scores depending on surgical method and the primary site of occurrence. On the surgical method, the limb salvage had more excellent outcomes (60.9) than the amputation (46.3). The tumor prosthetic replacement had notably higher scores (62.5) than any other methods. For the correlation coefficients on the MSTS and SF-36, the Physical Function had the highest degree of correlation. Excellent functions of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…Amputation can affect the patient's quality of life. Kim et al(Kim, Kwak and Chung, 2013) observed the quality of life of osteosarcoma patients with parameters SF36 and musculoskeletal tumor scores (MSTS) in the lower extremities. ijrp.org IJRP 2022, 106(1), 117-122;doi:.10.47119/IJRP1001061820223733 His research showed a significant relationship between MSTS and the SF-36 score in patients undergoing LSS (limb salvage surgery).…”
Section: Introductionmentioning
confidence: 99%
“…Amputation can affect the patient's quality of life. Kim et al(Kim, Kwak and Chung, 2013) observed the quality of life of osteosarcoma patients with parameters SF36 and musculoskeletal tumor scores (MSTS) in the lower extremities. ijrp.org IJRP 2022, 106(1), 117-122;doi:.10.47119/IJRP1001061820223733 His research showed a significant relationship between MSTS and the SF-36 score in patients undergoing LSS (limb salvage surgery).…”
Section: Introductionmentioning
confidence: 99%